PEREMPUAN DALAM TEKS-TEKS KEISLAMAN: Jalan Terjal Menuju Kesetaraan - Aldi Hidayat; Nur Fadiah Anisah; Ahmad Faaza Hudzaifah; Agustari (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract One thing that is often highlighted about Islam is it misperception and doctrine regarding women and their relationships with men. This spotlight drew responses from reformist thinkers by reinterpreting several doctrinal sources about women. No matter how re-interpretations have been put forward, the scriptural and textual of classical sources quite clearly obstruct such re-interpretations. There is a gap between equality as a universal ideal and explicit doctrine alongside concrete practice as reality. Facing this gap, the authors try to reconstruct the image of Islam regarding women using critical discourse analysis. For this reason, the authors offer two problem formulations; first, how did Islamic text depict women? Second, how did Islam determine the relational patterns of men and women? Answering these two formulations, the authors find two hypotheses that al-Qur'an itself give rise to a perceptive feedback about women which their characteristics that presented by al-Qur'an are in line with the stigmatic view of them. Apart from that, in the relational realm, al-Qur'an raises verses which then legitimize subordinating interpretations and practices towards women. Keywords: Women, Islam, Equality, Al-Qur'an